Rating of acoustic performance levels of NBR 15575 (2013) based on user perception: A case study in the Brazilian Amazon. Issue 4 (December 2017) - Santana, Wylliam Bessa; Maués, Luiz Mauricio Furtado; Soeiro, Newton Sure; Picanço, Marcelo de Souza
The new Brazilian building performance standard is a landmark in terms of housing regulation in Brazil. Nevertheless, due to the standard recent release, it becomes essential to make its requirements compatible with users' needs. This work has the objective to evaluate the acoustic performance requirements of buildings based on the users' perceptions of acoustic comfort. In order to do this, field tests were performed and surveys were applied to the users. The results demonstrate that the requirements defined by the Brazilian norm are unsuitable to meet the users' necessities. The correlation analysed shows a clear perception of the habitants in relation to the transmitted noise through the slabs and walls. These unsatisfactory results concern the acoustic performance of impact noise between slabs, as well as internal and external walls, showing that construction companies must implement new solutions that can provide greater acoustic performance to achieve acoustic comfort to the users.